Predicting Prognosis of Acute Pancreatitis Patient in a Tertiary Centre with Help of BISAP Scoring - Kanwar Singh Goel; Nikhil Goel; Sapna Singla (Disease and Health Research - New Insights Vol. 1, 2024)
Introduction: Acute pancreatitis is an acute inflammation of the prior normal pancreas. Gallstones are its leading cause, followed by alcohol; other etiological factors are hyperlipidemia, hereditary, hypercalcemia and post ERCP, etc. Its pathogenesis involves the activation of intrapancreatic digestive enzymes and the injury of acinar cells. Many scoring systems are available to assess the severity of acute pancreatitis, e.g., Ranson’s criteria, Glasgow score index, APACHE II and CTSI, but they have important limitations. BISAP score is a valuable tool in predicting severe Acute Pancreatitis in the early hours. BISAP score appears cheap, quick, and simple and hence, we conducted this study. Material and Methods: This prospective observational study was carried out in 83 patients at SGT Medical College, Gurugram, India from September 2018 to March 2021. Patients with an established diagnosis of acute pancreatitis as per the revised Atlanta classification and definition by the International Census 2012 were included in the study. BISAP scores were calculated from laboratory values and radiological findings. Results: In our patients with BISAP scores of 0, 1 and 2, there was no organ failure or mortality. At a score of 3, there was 1 (07.1%) organ failure and 1 (07.1%) mortality. At a score of 4, 4 (80.0%) patients had organ failure and 1(20.0%) patient died. We observed that the higher the BISAP score, the higher the percentage of severity, necrosis, organ failure, mortality and hospital stay. Our study revealed that with the cutoff value set at 3, the BISAP score has 39.6% sensitivity, 92.8% specificity, 60.3% PPV and 84.7% NPV. Conclusion: Our study recommends that at the time of admission, if the BISAP score is low, our worry is less, if the BISAP score is high, we should counsel the patient and attendants about possible severity, necrosis, organ failure and mortality in acute pancreatitis. Patients should be meticulously managed. The present study concludes the increased accuracy of the BISAP score for risk stratification.